All Questions Topic List
Limits Questions
Previous in All Question Next in All Question
Previous in Limits Next in Limits
Question Number 82950 by jagoll last updated on 26/Feb/20
limx→01+tanx3−1+sinx3x3=
Commented by mathmax by abdo last updated on 26/Feb/20
wehavea3−b3=(a−b)(a2+ab+b2)⇒a−b=(3a−3b)((3a)2+3ab+(3b)2)⇒⇒31x3(1+tanx−31+sinx)=1x3×(1+tanx−1−sinx(1+tanx)23+(1+tanx)(1+sinx)13+(1+sinx)23)⇒limx→0(...)=limx→013x3(sinxcosx−sinx)=13limx→0sinxx×1−cosxx2×cosx=13×1×12=16
Answered by john santu last updated on 26/Feb/20
limx→0tanx(1−cosx)x3×limx→01(1+tanx)23+(1+sinx)23+(1+tanx)(1+sinx)3=12×13=16
Terms of Service
Privacy Policy
Contact: info@tinkutara.com